ON THE FIND OF A PRIMITIVE HADROSAUROID DINOSAUR (ORNITHISCHIA, HADROSAUROIDEA) IN THE CRETACEOUS OF THE BELGOROD REGION - Arkhangelsky M.S.; Averianov A.O. (My University, 2003)
An isolated maxillary tooth and opisthocoelous anterior thoracic or posterior cervical vertebral centrum of a duck-billed dinosaur, Hadrosauroidea indet., are described. These parts originate from the marine Albian-Cenomanian deposits of the Stoilo iron ore quarry near the town of Staryi Oskol, Belgorod Region. This is the oldest record of a hadrosauroid dinosaur in Eastern Europe and one of the oldest representatives of this group in the world.
Keywords: Cretaceous; Mesozoic::Cretaceous::Upper::Cenomanian; Mesozoic::Cretaceous::Lower::Albian; Мезозой::Меловая::Нижний::Альбский; Мезозой::Меловая::Верхний::Сеноманский